2021
DOI: 10.3390/toxics9060131
|View full text |Cite
|
Sign up to set email alerts
|

Nanopesticides in Agriculture: Benefits and Challenge in Agricultural Productivity, Toxicological Risks to Human Health and Environment

Abstract: Nanopesticides are nanostructures with two to three dimensions between 1 to 200 nm, used to carry agrochemical ingredients (AcI). Because of their unique properties, the loading of AcI into nanoparticles offers benefits when compared to free pesticides. However, with the fast development of new engineered nanoparticles for pests’ control, a new type of environmental waste is being produced. This paper describes the nanopesticides sources, the harmful environmental and health effects arising from pesticide expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(82 citation statements)
references
References 87 publications
0
51
0
3
Order By: Relevance
“…Generally, nanoformulation and nanoencapsulation delivery formulas aim to enhance efficacy and maintain the durability of the active ingredients through a slowrelease mechanism on the targets [35,36]. There are a large number of studies revealing nano-delivery formulas of plant biopesticides [11,31,37,38]. Recently, many studies have reported efforts on the formulation of a nano-carrier of essential oils and plant extracts for antifeedant-targeted delivery against insect pests [39,40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, nanoformulation and nanoencapsulation delivery formulas aim to enhance efficacy and maintain the durability of the active ingredients through a slowrelease mechanism on the targets [35,36]. There are a large number of studies revealing nano-delivery formulas of plant biopesticides [11,31,37,38]. Recently, many studies have reported efforts on the formulation of a nano-carrier of essential oils and plant extracts for antifeedant-targeted delivery against insect pests [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics and properties of the antifeedant delivery system govern the feeding activity of phytophagous insects quantified by their insect feeding trace (consumed leaf area). Referring to a study focused on biopesticide nano-delivery formula, the pesticide loaded in colloidal or the encapsulation of botanical pesticides in nano-structured systems has emerged as an important tool to improve the quality of the formulations [11,[30][31][32][33][34]. However, botanical pesticides are usually soluble in an organic solvent, thus making a formula in water solvent requires additional ingredients to facilitate suitable delivery formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although many other previous works have also indicated that encapsulation of pesticides generally reduces their toxicity, this cannot be easily generalized to other nanopesticides. Therefore, research, development and innovation (RDI) in nanotoxicology is as important as its nanotechnology counterparts [ 23 , 24 , 25 ].…”
Section: Nanomaterials: Definition and General Properties For Nanotechnology Applicationsmentioning
confidence: 99%
“…It can be applied for several purposes, such as to promote improvements in human and animal health, create more durable consumer goods, increase agricultural and industrial productivity [1,2]. As a result, nanoparticles have been used for different goals, as a method to deliver fertilizers, in the development of antimicrobials against bacterial resistance, as environmental monitoring biosensors, and for pest control [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, metal and metal-oxide nanoparticles are being studied as materials with high potential for pest control [4,7,8]. Emphasis has been put on silver nanoparticles (AgNPs) for Antibiotics 2021, 10, 852 2 of 13 their easy synthesis, which can be performed by different methods and reducing/stabilizing agents, and versatility of application, due to their physical-chemical characteristics and toxicity on several insects [4,6,[9][10][11]. Currently, biological synthesis has been extensively explored for the production of AgNPs because it is sustainable, with high reproducibility and low production cost.…”
Section: Introductionmentioning
confidence: 99%